2007
DOI: 10.1016/j.neuroscience.2006.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and GABA levels in the oral part of rat pontine reticular formation are decreased by local and systemic administration of morphine

Abstract: Morphine, a μ-opioid receptor agonist, is a commonly prescribed treatment for pain. Although highly efficacious, morphine has many unwanted side effects including disruption of sleep and obtundation of wakefulness. One mechanism by which morphine alters sleep and wakefulness may be by modulating GABAergic signaling in brain regions regulating arousal, including the oral pontine reticular formation (PnO). This study used in vivo microdialysis in unanesthetized Sprague-Dawley rat to test the hypothesis that μ-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 68 publications
4
48
0
Order By: Relevance
“…In this way, reduction of the release of acetylcholine in the pontine GTF is one mechanism by which morphine inhibits REM sleep. In rats, morphine has been found to cause a concentrationdependent decrease in GABA levels of the oral part of the pontine reticular nucleus (PnO; Watson et al, 2007). Morphine may disrupt sleep by decreasing GABAergic transmission in the PnO.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, reduction of the release of acetylcholine in the pontine GTF is one mechanism by which morphine inhibits REM sleep. In rats, morphine has been found to cause a concentrationdependent decrease in GABA levels of the oral part of the pontine reticular nucleus (PnO; Watson et al, 2007). Morphine may disrupt sleep by decreasing GABAergic transmission in the PnO.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Li and van den Pol 17) reported that the sedative effect induced by narcotics is attributable to an inhibition of the orexin arousal system via m receptors. On the other hand, Watson et al 18) found that an increase in wakefulness time induced by a low dose of morphine is produced through the decreasing GABAergic transmission; therefore, the wakefulness-promoting effect induced by a low dose of morphine may be due to an inhibition of the GABAergic system. In addition, it is known that morphine via opioid receptors exerts anxiolytic effects, probably by interacting with the dopaminergic system by suppressing GABA inhibitory input to dopamine neurons, thereby augmenting dopamine release.…”
Section: Discussionmentioning
confidence: 99%
“…33 Opioids are the most widely used drugs for the treatment of pain, and negative side effects include disruption of the sleep-wake cycle. 57 GABA levels in the PnO are decreased by opioids 28 and increased by hypocretin-1. 13 Studies of GABA A -receptor point-mutated mice showing that systemic alterations of transmission at GABA A receptors can be antinociceptive 58 encourage continuing efforts to localize GABAergic modulation of nociception to specific brain regions.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…13,28 Briefly, rats were anesthetized with isoflurane (Abbott Laboratories, North Chicago, IL) and implanted with 3 screw electrodes (8IE36320SPCE, Plastics One, Roanoke, VA) for recording the cortical electroencephalogram (EEG). Three pair of EEG electrodes were placed using the following stereotaxic coordinates relative to bregma: 1.0 mm anterior and 1.5 mm lateral, 2.0 mm posterior and 1.5 mm lateral, and 2.0 mm posterior and 1.27 mm lateral.…”
Section: Animals Surgery and Conditioning Of Behaviormentioning
confidence: 99%
See 1 more Smart Citation